1977
DOI: 10.1080/15287397709529580
|View full text |Cite
|
Sign up to set email alerts
|

Absorption, distribution, and excretion of [14C] patulin by rats

Abstract: Adult rats of both sexes were given a single oral dose of [14C] patulin and were sacrificed at various time intervals from 4 hr to 7 days following administration of the mycotoxin. Two groups of rats were employed; the treated group had been exposed to daily oral doses of unlabeled patulin (dissolved in pH 5.0 citrate buffer) in utero and for 41-66 wk after weaning, while the controls were given the buffer only throughout gestation and for 38-81 wk after weaning. Approximately 49% of the administered 14C radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 11 publications
(11 reference statements)
0
9
0
Order By: Relevance
“…The concentrations required (2.5-5 µM) were similar to those (2.5 - 10 µM) effective in tumor cells [4]. In several countries the tolerance level of patulin contamination amounts to 50 µg/Kg (320 µM) [51] Following oral ingestion of radiolabelled patulin, some 36% of the label appeared in urine pointing to intestinal absorption [52]. Peritoneal administration of 1-3.75 mg/kg has been reported [53].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentrations required (2.5-5 µM) were similar to those (2.5 - 10 µM) effective in tumor cells [4]. In several countries the tolerance level of patulin contamination amounts to 50 µg/Kg (320 µM) [51] Following oral ingestion of radiolabelled patulin, some 36% of the label appeared in urine pointing to intestinal absorption [52]. Peritoneal administration of 1-3.75 mg/kg has been reported [53].…”
Section: Discussionmentioning
confidence: 99%
“…Peritoneal administration of 1-3.75 mg/kg has been reported [53]. From all tissues, erythrocytes displayed the stongest retention of the label [52]. …”
Section: Discussionmentioning
confidence: 99%
“…A study by Dailey et al in both male and female rats showed 36% PAT was recovered in the urine 7 days post-administration 64 . This study found PAT accumulated in blood rich organs specifically the kidney, liver, erythrocytes and spleen.…”
Section: Methodsmentioning
confidence: 95%
“…Results of metabolic studies of C-patulin show that it is excreted principally via the faeces and urine. The major retention and storage site is the erythrocyte (Dailey et al, 1977;McKinley and Carlton, 1991). Patulin has an inhibiting effect on several biochemical parameters such AT-Pase, alkaline phosphatase, aldolase and hexokinase activity.…”
Section: Absorbtion Distribution Metabolism Excretion and Biochemimentioning
confidence: 99%